Considerations on Water Network Construction in Beijing - WANG Tao; LI Liqin; WU Xia; WANG Yan (Renmin Zhujiang)
According to the new requirements and new direction of national water network construction, combined with the practice of Beijing water network planning, the situation and demand of Beijing (as a national center city) water network were analyzed based on the new requirements of the strategic positioning of the four centers in Beijing. By taking the "nature-society" binary water cycle as the theoretical foundation, this paper proposed a significant network form of "five veins and five lines, three rings and ten networks, five districts and four reservoirs" in space, with five major water systems as the foundation, water diversion projects as the channels, transmission and distribution channels as the veins, and regulation and storage projects as the nodes. Functionally, it played a comprehensive role in flood control and disaster reduction in river basins, water ecological protection, multiple water source protection, water supply and drainage safety guarantee, offering ideas and work suggestions for Beijing water network architecture and providing a reference for the construction of water network projects in large and medium-sized cities in the northern region.